Division of Listeria monocytogenes Serovar 1/2a Strains into Two Groups by PCR and Restriction Enzyme Analysis - Unnerstad, Helle (American Society for Microbiology, 1999)
Altogether, 100 strains of Listeria monocytogenes serovar 1/2a isolated from humans, animals, food, and the environment were typed by a combination of PCR and restriction enzyme analysis (REA). A PCR product of 2,916 bp, containing the downstream end of the gene inlA (955 bp), the space between inlA and inlB (85 bp), and 1,876 bp of the gene inlB, was cleaved with the enzyme AluI, and the fragments generated were separated by gel electrophoresis. By this method two different cleavage patterns were obtained. Seventy of the 100 strains shared one restriction profile, and the remaining 30 strains shared the second one. No relation was found between the types differentiated by PCR-REA and the origins of the strains.